SecGPSR: A Secure GPSR Protocol for FANET Against Sybil and Gray Hole Attacks - Mauro Tropea; Mattia Giovanni Spina; Abderrahmane Lakas; Panagiotis Sarigiannidis; Floriano de Rango (IEEE Access)
In recent years, drones have become increasingly prevalent in a wide range of applications, performing complex and critical tasks. To accomplish these tasks, drones cooperate by forming a Flying Ad-Hoc Network (FANET) using specific routing protocols for communication. However, most of the routing protocols used in this type of network lack appropriate built-in security mechanisms, which creates numerous security challenges and concerns. To reduce the resulting security vulnerabilities and mitigate the impact of potential attacks, it is crucial to address these challenges before any deployment of FANETs. In this paper, Sybil and Gray Hole attacks in FANET are analyzed. A commonly used and scalable routing protocol, namely the Greedy Perimeter Stateless Routing (GPSR) protocol, has been considered. After demonstrating the magnitude of the damage caused by the two attacks, a mitigation technique is proposed for each of them resulting in a secured version of the GPSR, namely secGPSR. The robustness of secGPSR is validated through simulation using Omnet++ presenting the results that show the effectiveness of secGPSR in counteracting Sybil and Gray Hole attacks in FANET.